Opal’s Dainties Sdn. Bhd. / Naufal Ashroff - Ashroff, Naufal (2020)
Opal’s Dainties Sdn. Bhd. Is a bakery and café that offers to its customers varieties of bakeries goods with premium quality but still offering very reasonable price. Opal’s Dainties will be using fine ingredients to make our products so that our customers may enjoy the best of service. By including a very aesthetically pleasing café, customers may also enjoy dine-in our products with relaxing environment at the café. Our targeted customers mainly on the nearby area which consists of university students, office workers and general public. This is because our store is located near Sunway University, Monash University, office districts and residential area nearby. By offering various types of bakeries, we can tend to our customer needs and wants. Office workers may like breads for quick bites or as a snack, whilst university students would probably enjoy more of the café and the pastries, leisurely spending their time there. We can also accommodate certain occasions by making cakes if it was ordered by the customer. Our physical store is easy to access, with spacious parking lots around the area and just a walking distance from the universities or the office district. Customers beyond the area can easily search our café and bakery through application such as Waze or Google Maps to find it more efficiently. We also provide our menu at the website so that customers may up to date with our latest promotions, discounts or to order our cakes for occasions.